Microplastic Pollution: The Escalating Environmental and Health Hazards Threatening Ecosystems and Human Well-being - Naganna, Harshith; Rao, Kumble Prakash Rao Tejas; Lokanathan, Tejaswi Hiremarali; Ravishankar, Mathada Vamadevaiah (International Journal of Pharmaceutical Investigation, 2026)
Plastic is found with its wide applications worldwide to fulfil our domestic and industrial needs. Its vast diversified usability and unscientific disposal patterns cause tireless accumulation of various forms of plastic waste materials in our surroundings. Anthropogenic waste is causing an increasing threat to the environment and to the public. The global production of plastic waste is expected to increase from the current 350 million metric tons to 1200 million metric tons per by the year 2050. Its poor biodegradability and improper and unscientific disposal methods lead to its undue environmental segregation and bioaccumulation due to its constant contact and exposure. Based on their particle size they are classified as macroplastic, microplastic, mesoplastic, nanoplastic, etc. Smaller the particle size greater will be the potential to breach into the bio/ecosystem and can cause environmental discrepancies and threaten the food chain system which involves the chain of creatures that are consumed in an orderly manner for their survival. Inevitable human exposure towards diversified varieties of plastic polymers causing severe health and environmental hazards. It's improper and inadequate recycling cause undue infiltration and vast accumulation in various layers of the ecosphere. They enter human biological system through various pathways through inhalation, ingestion, and dermal contact of plastic pollutants, can produce hazardous impacts. These pollutants jeopardize the lives of billions of living beings directly or indirectly. Micro plastic pollution and its constraints in disposal is a great challenge to the modern era; if they once released into the environment, it is almost impossible to retrieve them back. Their constant and subtle dissemination into the biological system causing subtle to grievous impacts on all living beings. Microplastics are currently being considered intensely from the point of their potential hazardous health effects. Its diversified consequences threatening various body systems like respiratory, digestive, nervous, endocrine, skin, etc., along with its effect during early foetal life also will be highlighted in the present review
Keywords: Anthropogenic; Ecosystem; Microplastic; Polymer.